STRATEGI PEMASARAN PRODUK DAN LAYANAN UPTD BALAI PELAYANAN DAN SAINTIFIKASI JAMU (BPSJ) KOTA PEKALONGAN - Parasamya Dewi Cipta; Danang Satrio (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2023)
This study aims to analyze strategies marketing products and services at UPTD BPSJ Pekalongan City. Nowadays, when most people prefer new products, promoting traditional products, especially UPTD BPSJ Pekalongan City, is difficult. This research employed a descriptive qualitative method.The analysis was conducted at UPTD BPSJ Pekalongan City. The results of the study show that the success of the marketing strategy of UPTD BPSJ Pekalongan City products and services is by doing a combination of conventional and digital promotions. Keywords: Marketing strategy, traditional products